Evaluation of therapeutics management patterns and glycemic control of pediatric type 1 diabetes mellitus patients in Turkey: A nationwide cross-sectional study - BEREKET, ABDULLAH (ELSEVIER IRELAND LTD, 2016)
Aims: To evaluate the management strategies, glycemic control and complications of pediatric type 1 diabetes mellitus (T1DM) patients in Turkey. Methods: Study included 498 patients with T1DM between the ages 1-18. Data provided from patients' hospital files were recorded on standard case report forms by applicant clinicians within the 3 months of data collection period between October 2012 and July 2013. Results: Mean age of patients was 11.3 +/- 3.8 years. Mean duration of DM was determined as 3.7 +/- 3.1 years. Majority of patients (85.5%) used basal/bolus injection (BBI), and 6.5% used continuous subcutaneous insulin infusion pump. Assessment of glycemic control based on HbA1c levels showed that 29.1% of patients had an HbA1c value <7.5% (58 mmol/mol), 16.1% had a value between 7.5% (58 mmol/mol) and 8% (64 mmol/mol), 19.1% had a value between 8.1% (64 mmol/mol) and 9%(75 mmol/mol) and 35.7% a value >9%(75 mmol/mol). Hypoglycemia was reported in 145 (29.1%) patients and the number of severe hypoglycemic attacks in the last 3 months was 1.0 +/- 2.4. Taking into consideration the carbohydrate count and insulin correction dose and parents with high socioeconomic status was related to have better glycemic control. The most common comorbidities were Hashimoto's thyroiditis/hypothyroidism (6.2%) followed by celiac disease (3.8%), epilepsy(1.2%), and asthma(1.0%). Conclusions: BBI insulin therapy is widely used among pediatric T1DM patients in Turkey. However, despite improvements in treatment facilities and diabetic care, glycemic control is not at a satisfactory level. Therefore, new and comprehensive initiatives require for pediatric T1DM patients with poor glycemic control. Promoting use of carbohydrate count and insulin correction doses may improve the glycemic control of pediatric T1DM in Turkey. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Type 1 diabetes; Children; Treatment; Glycemic control; HbA1c; CHILDREN; ASSOCIATION; PREVALENCE; REGION; RISK